ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PENDENGAR RADIO PUBLIK MIMIKA DI KABUPATEN MIMIKA - Robertho Kailey; Habel Taime (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to determine the analysis of the factors that influence the loyalty of Mimika public radio listeners in Mimika Regency. The research method used in this research is descriptive method, namely a research method that describes or describes something, for example circumstances, conditions, situations, activities, and others. In this study the data collection techniques used were observation and questionnaires. the factors that influence the loyalty of Mimika public radio listeners in Mimika Regency, the analysis used in this research is Confirmatory Factor Analysis. The results of the study show that the Emphaty variable dominates or is very influential in this study, meaning that Mimika public radio listeners still show their loyalty because of their high sense of empathy for Mimika public radio in the current digitalization era